Incidence and outcomes of acute kidney injury in term neonates with hypoxic ischemic encephalopathy: an observational study - ., Zainab; Ali, Syed Manazir; Afzal, Kamran (International Journal of Contemporary Pediatrics, 2022)
Background: Hypoxic ischemic encephalopathy (HIE) is one of the devastating birth related complication. It predisposes the babies to serious outcomes, an important one being acute kidney injury (AKI). Methods: A prospective crossectional observational study was conducted in Jawaharlal Nehru Medical College and Hospital, AMU, Aligarh between November 2019 and October 2020. 153 term neonates with perinatal asphyxia were enrolled. HIE staging and AKI staging done according to Sarnat and Sarnat classification and KDIGO classification respectively. Outcome in terms of recovery, persistent deranged renal function at discharge or mortality noted. Results: In our study, incidence of Acute Kidney Injury in Hypoxic Ischemic Encephalopathy neonates was 37.7%. There was around 39-fold increase risk of developing AKI in HIE stage III versus HIE stage I. Mortality rate was found to be 51.6%. Mortality was significantly high in HIE stage III. There was around 5-fold increase risk of mortality in HIE neonates with AKI as compared to HIE neonates without AKI. 50% of the subjects who had AKI and discharged recovered of renal function before discharge and 50% recovered at 1 month follow up. In addition, there was no association found between different stages of HIE with different stages of AKI. Conclusions: It is better to screen all the birth asphyxia cases for AKI so that they can be detected early and managed accordingly.